Antidiabetic effects of Semecarpus anacardium leaf extracts in streptozotocin-induced diabetes in rats - Vikhe, Sunayana; Sukhadhane, Pradnya; Vikhe, Rahul; Bornare, Snehal L; Dhavane, Shweta S (Journal of Applied Pharmaceutical Research, 2024)
Background: A class of metabolic diseases known as diabetes mellitus is typified by persistently high blood sugar levels brought on by malfunctions in the production or function of insulin. Conventional treatments frequently have drawbacks and side effects, prompting interest in alternative treatments such as herbal remedies. Semecarpus anacardium, known for its medicinal properties, was investigated for its antidiabetic potential. Methods: Semecarpus anacardium leaves were collected, authenticated, and extracted using various solvents. The ethanol extract was subjected to preliminary phytochemical screening, HPLC-DAD analysis, and tested for antidiabetic activity in streptozotocin-induced diabetic rats. Biochemical parameters, histopathological studies, and lipid profiles were analyzed over a 20-day period. Results: The ethanol extract exhibited the highest yield (13.53% w/w) and contained significant amounts of bioactive compounds, including flavonoids and alkaloids. In diabetic rats, the ethanol extract at 200 mg/kg significantly reduced blood glucose levels from 333.35 ± 5.2 mg/dL to 121.68 ± 7.56 mg/dL. Highly significant results were obtained in lipid profiles, with total cholesterol reducing from 176.82 ± 1.07 mg/dL to 103.69 ± 2.85 mg/dL and triglycerides from 188 ± 5.73 mg/dL to 97.17 ± 8.41 mg/dL. Histopathological analysis showed partial restoration of pancreatic islets and reduced fibrosis, indicating the protective effects of the extract. Conclusion: The ethanol extract of Semecarpus anacardium leaves demonstrates significant antidiabetic and lipid-lowering effects in streptozotocin-induced diabetic rats. These findings support the potential of this plant as a natural therapeutic agent for diabetes management, warranting further research for clinical application.